2018
DOI: 10.1021/acs.jpcc.8b05531
|View full text |Cite
|
Sign up to set email alerts
|

Mn–O–O Electron Spin Flip Mechanism Triggered by the Visible-Light Irradiation for the Generation of an Active Mn(V)–Oxo Complex from O2: Insight from Density Functional Calculations

Abstract: We reveal a new activation mechanism of O2 by electron spin flip for the formation of a high-valent Mn­(V)–oxo corrolazine complex under O2 atmosphere and visible-light irradiation conditions. Ab initio calculations show that a loosely associated triplet complex from a quintet manganese corrolazine with a triplet O2 is formed initially in reaction. The subsequent strong bonding interactions between dioxygen with the manganese corrolazine, triggered by the visible-light irradiation, give rise to an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(49 reference statements)
2
8
0
Order By: Relevance
“…In addition, the energy of structure 11 was the lowest, again proving that it was the most stable. Furthermore, Table 1 shows the bond lengths of Mn-O and O-O were 1.617 and1.265 Å, respectively, which are similar to the results obtained in our previous study ( Zhu et al, 2018 ), indicating that the [Mn]-O-O moiety in structure 11 has strong oxidation ability. Therefore, we chose structure 11 as the RC to further explore the degradation of BaP.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the energy of structure 11 was the lowest, again proving that it was the most stable. Furthermore, Table 1 shows the bond lengths of Mn-O and O-O were 1.617 and1.265 Å, respectively, which are similar to the results obtained in our previous study ( Zhu et al, 2018 ), indicating that the [Mn]-O-O moiety in structure 11 has strong oxidation ability. Therefore, we chose structure 11 as the RC to further explore the degradation of BaP.…”
Section: Resultssupporting
confidence: 87%
“…Our group has recently reported that Mn-corrolazine can activate oxygen in the air via an electron spin-flip mechanism under visible light irradiation, which forms a singlet [Mn]-O-O species with terminal radical characteristics ( Zhu et al, 2018 ). In fact, corrole has been widely used in many fields ( Zhu and Liang, 2015 ; Zhu et al, 2016 ; Li and Cao, 2018 ; Lvova et al, 2018 ; Liang et al, 2019 ; Zheng et al, 2020 ; Dedic et al, 2021 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies, [46,[50][51][52] reaction. [52][53][54] Moreover, the reaction energy of 72.3 kcal/mol will promote the reaction to the right thermodynamically.…”
Section: The Reaction Of [Mn] O O Corrolazine With Ch 4 Under the Fmentioning
confidence: 94%
“…Prokop and Goldberg's experiment and our density functional theory (DFT) calculations show that the high-valence Mn(V)-oxo corrolazine complex can be conveniently formed by the oxidation of the Mn(III) corrolazine with O 2 under visible light irradiation, while organic substrates are oxidized through continuous H-abstraction and rebound processes. [45,46] Therefore, Mn corrolazine is of great significance in catalysis because it can directly use cost-effective, abundant, and environmentally friendly molecular O 2 as an oxidant. Moreover, in the process of Mn-corrolazine-catalyzed oxidation of organic substrates, the rate-determining step is through the Mn-corrolazine O O species bearing the instinct Mn O reaction axis.…”
mentioning
confidence: 99%
“…With sustained efforts of many scientists discovering 2D monolayer materials with remarkable properties, several chemical systems like group IV and group III–V element compounds and transition metal oxides have been considered as promising systems for searching 2D monolayer materials . With respect to monolayer materials, they reveal a good flexibility, large photoluminescence, , valley polarizations, strong exciton effects, , and strong SHG responses. As such, several applicable monolayers have been developed, including insulators (hexagonal boron nitride (h-BN)), semiconductors (MoS 2 , black phosphorus (BP), etc.…”
Section: Introductionmentioning
confidence: 99%